Oh, Yuck! : The Encyclopedia of Everything Nasty - Masoff, Joy; Illustrated by Sirrell, Terry (New York Workman Publishing Company, Inc., 2000)
An alphabetical collection of articles about disgusting things, from acne, ants, and bacteria to worms, x-periments, and zits.
Include Colour Illustrations and Index
Keywords: Aversion -- Handbooks, vade-mecums, etc -- Curiosities and wonders